The Role of Guidance and Counseling Services in Individual Counseling During The Covid-19 Pandemic - Astuti, Laily Puji (Universitas Mercu Buana Yogyakarta, 2021)
The primary role of the counsellor during the Covid-19 pandemic is expected to be able to formulate individual counselling services that are in accordance with the needs of students today. One of the guidance and counselling services is an individual counselling service which refers to Permendikbud Number 111 of 2014 to obtain limited information about individual counselling. It is hoped that the implementation of guidance and counselling will be able to implement individual counselling services properly. Guidance and counselling must be able to: 1) Prioritize the welfare of the counselee, 2) Able to develop the counselee's diversity of competency skills, 3) Develop information and emotional control skills, 4) Have high resilience in dealing with one's own problems and counselee problems. Individual counselling services are teacher guidance and counselling services in schools to help students solve problems about truancy, interaction with friends, personal problems and career studies. The function of individual counselling services in guidance and counselling can help students in overcoming problems, getting change, direction and support and better attention. Therefore, the role of guidance and counselling in individual counselling services is very important in guidance and counselling in schools. So the counsellor must have the ability to guide, understand the characteristics of students well so that the counsellor can provide optimal guidance services to students.